Understanding the politics and processes of introducing sustainable livelihoods on the island of Malapascua, Philippines - Innocenzi, Livia (The University of Edinburgh, 2014)
This study stems from the research and work that was carried out in Malapascua, Philippines, with a local organization. This consisted of designing and implementing sustainable livelihood strategies to increase environmental awareness, improve community well-being, and financially sustain the organization and its projects. The aim of this investigation thus became answering: ‘why is it that projects that try to implement sustainable livelihoods face resistance and general lack of enthusiasm from the local community?’ It also sought to examine three related sub-themes: the role and impact of culture, the role and impact of tourism, and notions of eco-imperialism. This was carried out as a single ethnographic case study, using participant observational analysis, semi-structured interviews and questionnaires. Ultimately, a combination of intertwined factors were found to act as deterrents to the successful implementation of such efforts, notably local culture and values, low levels of education and environmental awareness, an absence of leadership and initiative, low community capital, poor community engagement, and poor stakeholder communication. In order to monitor the programs’ progress over time and either reinforce or contend the current findings, future research should broaden this study’s scope and include longitudinal and cross-cultural assessments and comparisons.
Keywords: sustainable livelihoods; Philippines; culture; human-environmental relations; tourism; MSc Environment & Development